ANALISIS KESANTUNAN BERBAHASA PADA KEGIATAN PEMBELAJARAN KELAS VIII E SMPN 2 KOTA BENGKULU TAHUN AJARAN 2016/2017 - Ayu Wulan Dari; Dian Eka Chandra; Marina Siti Sugiyati (Universitas Bengkulu, 2017)
This research has objective to know deviation and compliance of language politeness principle in class discussion activity, Indonesian language subjects, in terms of word selection, and polite way of discussion to students of class VIII E SMPN 2 Kota Bengkulu and the implication in learning Indonesian language. Type of research used by the researcher is descriptive method with qualitative approach. The subjects of this study are students of class VIII SMPN 2 Kota Bengkulu, on the subjects of Indonesian language. The results of this study indicate that the data of deviation of language politeness principle consists of four maxims, including maxim of wisdom, appreciation, generosity, and simplicity. The deviation of the principle of politeness consists of the deviation of one maxim and two different maxims at once in one speech. The deviation of the principle of modality of two maxims consists of deviations of the principle of generosity of maxim of generosity and of appreciation, wisdom and generosity, and wisdom and reward. Furthermore, the data on the compliance of the principle of linguistic politeness consists of six maxims, including maxim of wisdom, reward, generosity, simplicity, consensus, and conclusions. Adherence to the principle of politeness in the form of one maxim, two maxims, and three different maxims at once in one speech. The adherence to the principle of modality of two maxims consists of adhering to the principle of maximized politeness of wisdom and generosity, wisdom and simplicity, respect and wisdom, respect and consent, and appreciation and simplicity.